Adherence to Healthy Lifestyle and Attenuation of Biological Aging in Middle-Aged and Older Chinese Adults. (30th July 2021) - Fan, Junning; Yu, Canqing; Pang, Yuanjie; Guo, Yu; Pei, Pei; Sun, Zhijia; Yang, Ling; Chen, Yiping; Du, Huaidong; Sun, Dianjianyi; Li, Yanjie; Chen, Junshi; et al.
Abstract: Background: Little is known about the effects of lifestyle modification on biological aging in population-based studies of middle-aged and older adults. Method: We examined the individual and joint associations of multiple lifestyle factors with accelerated biological aging measured by change in frailty index (FI) over 8 years in a prospective study of Chinese adults. Data were obtained on 24 813 participants in the China Kadoorie Biobank on lifestyle factors and frailty status at baseline and at 8 years after baseline. Adherence to healthy lifestyle factors included nonsmoking or quitting smoking for reasons other than illness, avoidance of heavy alcohol consumption, daily intake of fruit and vegetables, being physically active, body mass index of 18.5–23.9 kg/m 2, and waist-to-hip ratio of <0.90 (men)/0.85 (women). FI was constructed separately at baseline and resurvey using 25 age- and health-related items. Results: Overall, 8 760 (35.3%) individuals had a worsening frailty status. In multivariable-adjusted logistic regression analyses, adherence to healthy lifestyle was associated with a lower risk of worsening frailty status. Compared with robust participants maintaining 0–1 healthy lifestyle factors, the corresponding odds ratios (95% CIs) were 0.93 (0.83–1.03), 0.75 (0.67–0.84), 0.68 (0.60–0.77), and 0.55 (0.46–0.65) for robust participants with 2, 3, 4, and 5–6 healthy lifestyle factors. The decreased risk of frailty status worsening by adherence to healthy lifestyle factors was similar in both middle-aged and older adults, and in both robust and prefrail participants at baseline. Conclusions: Adherence to a healthy lifestyle may attenuate the rate of change in biological aging in middle-aged and older Chinese adults.